EFFECTING OF CELEBRITY ENDORSEMENT ON CUSTOMERS’ ATTITUDE TOWARDS ADVERTISEMENT AND PURCHASE INTENTION: A CASE STUDY OF A SKINCARE SOAP IN THAILAND - Natithamapimuke, Attaphorn; Nuangjamnong, Chompu (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2022)
This research paper is conducted to inspect the effect of celebrity endorsement which includes 3 elements of celebrity source credibility which are celebrity attractiveness, celebrity trustworthiness, and celebrity expertise on customers’ attitudes towards advertisements and also their purchase intention. The sample of 400 respondents was drawn using an online questionnaire. After getting the responses, the data is analyzed using descriptive analysis together with multiple linear regression. The research found out that all of the endorsed celebrity elements have a positive impact on customers’ attitudes towards advertisement, however, for customer’s purchase intention, only 2 of 3 elements that do not include celebrity trustworthiness positively affect customer’s purchase intention. In addition, this research also states about possible further studies and recommendations which mainly focus on eliminating restrictions and limitations considering a variety of respondents limited only to Bangkok, Thailand.